DERADICALIZATION THROUGH UNDERSTANDING THE VALUE OF RELIGIOUS MODERATION IN MA'HAD DARULROHMAH PATTANI THAILAND - Sudarat Phan-ae; Asrori Asrori; Rusman Rusman (Universitas Islam Lamongan, 2023)
Internalization of the value of religious moderation or wasatiyah as a form of resistance to extremism. The notion of radicalism caused by an internal misunderstanding of religious texts can be stemmed by a moderate understanding of Islam. This study aims to find out how the values of religious moderation are in Maahad Darulrahmah Pattani Thailand and how the method of cultivating religious moderation values is in Maahad Darulrahmah Pattani Thailand. This study used descriptive qualitative, observational data collection techniques, and interviews with the research subject, the Head of Maahad Darulrahmah Pattani Thailand. The results of the first study, the values of Religious Moderation in Maahad Darulrahmah Pattani Thailand are as follows: Tawassuth, Tawazun, I'tidal, Tasamuh, Musawah, Shura, Islah, Aulawiyah, Tatawwur wa ibtikar, Tahadhdhur, Al-Muwathanah, Qudwatiyah. The two methods of instilling the value of religious moderation in Maahad Darulrahmah Pattani Thailand are as follows: Madrasa, Halaqah Method, Hidden curriculum